ANALISIS SEMIOTIKA VISUALISASI TOKOH UTAMA SERIAL KARTUN TOM AND JERRY (Verba Vitae Unwira, 2020)
A Semiotic Analysis on The Visualization of The Main Characters of The Cartoon Tom and JerryThis study was conducted to uncover the symbolic meanings-denotation and connotation- as well as myth presented  in the visualization of cartoon characters- Tom and Jerry. The type of this study is interpretative-qualitative in which a Semiotic theory was applied. Roland Barthes’s semiotic analysis technique was used to analyze the data. The results of the analysis confirm that the visualization of the characters-Tom and Jerry- contain denotative and connotative meanings as well as myths as found in everyday life. The main figures Tom- the cat, and Jerry- the mouse, depict the social-constructed reality of human life in that sometimes  they perform peace as well as war. The big body building of Tom can be interpreted as those who have power and authority. On the other hand, Jerry is represented by a tiny mouse which can be interpreted as those who are clever, resilient and always try to avoid problem. However, many times he is a problem maker.
Keywords: Semiotics; Social Construction of Reality; Cartoon